Localization of the amino acid substitution site in a new variant of human serum albumin, albumin Mexico-2 - Franklin, Samuel G. (1980)
Using an electrophoretic screening procedure, we have discovered that two species of human serum albumin Mexico occur that are indistinguishable by conventional electrophoretic methods. We suggest that these species be referred to as albumins Mexico-1 and Mexico-2. Isolation and determination of the partial sequence of the cyanogen bromide fragment of albumin Mexico-2 that differs from the corresponding fragment of the common albumin A revealed this variant to arise from at least a glycine/aspartic acid substitution at position 550. This region of the albumin molecule is involved in the binding of the fatty acid, palmitate.